2013
DOI: 10.1177/0146167213510323
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Prototypes and Dimensions of Honor

Abstract: Research evidence and theoretical accounts of honor point to differing definitions of the construct in differing cultural contexts. The current studies address the question "What is honor?" using a prototype approach in Turkey and the Northern United States. Studies 1a/1b revealed substantial differences in the specific features generated by members of the two groups, but Studies 2 and 3 revealed cultural similarities in the underlying dimensions of self-respect, moral behavior, and social status/respect. Rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 88 publications
(130 citation statements)
references
References 35 publications
7
123
0
Order By: Relevance
“…In line with the idea that one's self-esteem is related to living up to honor concerns, the most commonly used honor-scale measures endorsement of honor values by asking participants to rate the extent to which honor-relevant behavior damages one's self-esteem (Rodriguez Mosquera, Manstead, & Fischer, 2002a). However, the link between honor and self-esteem should not be universally assumed, given that cross-cultural research has shown that the salience of honor concerns differs across cultures (e.g., Cross et al, 2014;Uskul, Cross, Sunbay, Gercek-Swing, & Ataca, 2012). In the current study, our aim was to examine the contribution of three types of honor concerns (integrity, reputation, and family honor) on self-esteem in two typical low-honor groups (Northern European Americans, Dutch) and one typical high-honor group (Turkish).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the idea that one's self-esteem is related to living up to honor concerns, the most commonly used honor-scale measures endorsement of honor values by asking participants to rate the extent to which honor-relevant behavior damages one's self-esteem (Rodriguez Mosquera, Manstead, & Fischer, 2002a). However, the link between honor and self-esteem should not be universally assumed, given that cross-cultural research has shown that the salience of honor concerns differs across cultures (e.g., Cross et al, 2014;Uskul, Cross, Sunbay, Gercek-Swing, & Ataca, 2012). In the current study, our aim was to examine the contribution of three types of honor concerns (integrity, reputation, and family honor) on self-esteem in two typical low-honor groups (Northern European Americans, Dutch) and one typical high-honor group (Turkish).…”
Section: Introductionmentioning
confidence: 99%
“…When asked to define honor, people around the globe report similar components of honor (Cross et al, 2014;Guerra, Giner-Sorolla, & Vasiljevic, 2012). Specifically, they report personal aspects related to integrity (e.g., being trustworthy, doing the right thing, being loyal to one's own principles) and social reputation (e.g., having a positive social image and status).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of Turkish and North American honor prototypes, Cross and her colleagues (Cross, Uskul, Gercek-Swing, Sunbay, & Ataca, 2010) were able to identify four dimensions of the honor construct that were comparable in these two cultures (i.e., Turkey, an honor culture, and Midwestern United States, a dignity culture). These four dimensions were obtained in a factor analyses of honor concepts (which were generated by Turkish and American college students) rated for their centrality by Turkish and American participants.…”
Section: Honor In Turkish Latina/o and The North American Culturesmentioning
confidence: 99%
“…Scotts ' (1965) original values inventory is composed of 12 subscales of intellectualism, kindness, social skills, loyalty, academic achievement, physical development, status, honesty, religiousness, self-control, creativity, and independence. Only intellectualism, physical development, and creativity subscales were used in this study, because the other nine subscales of Scott's (1965) inventory tap constructs that are similar to honor prototypes of Turkish and American cultures obtained by Cross et al (2010). For participants who are in the self-affirmation condition, their most highly rated value among the three (their score in the first session) was used as the topic of the self-affirmation manipulation.…”
Section: Heatherton and Polivy's (1991) State Self-esteem Scale (Ssesmentioning
confidence: 99%
See 1 more Smart Citation